PLANT WASTEWATER TREATMENT IN THE NATIONAL UNIVERSITY OF SAN MARCOS, LIMA PERU - Erazo-Erazo, R. (2000)
This work is aimed at developing a design of a wastewater treatment plant to treat wastewater released from the Campus of the University of San Marcos in Lima - Perú. An anaerobic treatment of sewage has been designad to treat a load of 1.00 L/s of wastewater, containing a DBO5 of 220 mg/L. The required biorreactor has a capacity of 10.8 m3 , wich will operate at high yield compared to the standard processes of treatment. lt has been demonstrated that this process is economically and technically feasible, and the total cost of implementing, this project has been calculated in US$ 45 000, using locally available corrosion resistant material.